When the Pandemic Will Be Over: Lots of Hope and Some Concerns - Domenico Azzolino; Giulia Carla Immacolata Spolidoro; Alessandra Mazzocchi; Carlo Agostoni; Matteo Cesari (Geriatrics, 2022)
The COVID-19 pandemic significantly threatened healthcare systems worldwide. The worst-hit population has been represented by older people with underlying chronic comorbidities, while children and adolescents developed mild or asymptomatic forms of the disease. However, certain medical conditions (i.e., obesity, respiratory, or neurological or immune disorders) may increase the risk for poor health outcomes even in young and middle-aged people. Beyond the direct negative effects of the infection, the pandemic posed several health challenges through an increase in psycho–social issues (i.e., anxiety, depression, fatigue, sleep alterations, loneliness, reduced assistance, and loss of income). Accordingly, the pandemic is negatively impacting the accumulation of the functional reserves of each individual, starting from early life. With the long-term effects of the pandemic to be seen in the coming years, clinicians must be prepared to manage such high clinical complexity of people they encounter, through the implementation of multidimensional and multidisciplinary interventions.